Comparison of the favorable gain values of genetic improvement among Indonesian grade cow breeds selected for agrotechnopark intensification - Paputungan, U.; Hendrik, M. J.; Siswosubroto, S. E. (Journal of the Indonesian Tropical Animal Agriculture, 2021)
This research was aimed to compare the small and big truncation point proportions intended to evaluate gain values of genetic improvement for Indonesian Local cow breed groups selected for Agrotechnopark (integrated bio-cycle farming system) intensification. Animal live weights were collected from 674 Indonesian grade breed cows kept by local household farmers in North Sulawesi province. Data of cows were corrected by adjusting to six years old ages. All cows were divided into three breed groups with different genetic compositions of Bali breed cow generation (BG) of 207 cows, Ongole grade cow generation (OG) of 189 cows, and Local grade cow generation (LG) of 178 cows. The genetic improvements of BG, OG and LG were analyzed involving selection intensity (i), accuracy of selection (r), and standard deviation (SD) of breed group traits under selection. Results of this study showed that the critical components was genetic development of local grade breeds by choosing small proportion of 10% truncation point for Agrotechnopark intensification of selected elite cows groups among BG, OG and LG populations with the positive live weight gains of 58.6 kg, 23.15 kg, and 28.62 kg per generation, respectively compared with larger percentages of 20% and 30% proportions of truncation points.